2011
DOI: 10.1007/s10658-011-9886-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes differentially expressed in Pinus pinaster and Pinus pinea after infection with the pine wood nematode

Abstract: The purpose of this study was to compare the response to infestation by the pine wood nematode (PWN) Bursaphelenchus xylophilus between Pinus pinaster and P. pinea at an initial stage of the disease, 3 h after inoculation. The PWN is the causal agent of pine wilt disease and is destroying pine forests all over the world. In Portugal its main host is the maritime pine, P. pinaster, and its vector is the longhorn beetle Monochamus galloprovincialis. Interestingly, this disease does not seem to affect the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…This gene had previously been identified in our laboratory to be involved in the response to PWD [16]. Additionally, the analysis confirmed the differential expression of the malic oxidoreductase (also an antioxidant enzyme) and ricin B-related lectin, that belong to a class of participants in the general defense against a multitude of plant pathogens [44].…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…This gene had previously been identified in our laboratory to be involved in the response to PWD [16]. Additionally, the analysis confirmed the differential expression of the malic oxidoreductase (also an antioxidant enzyme) and ricin B-related lectin, that belong to a class of participants in the general defense against a multitude of plant pathogens [44].…”
Section: Resultssupporting
confidence: 53%
“…Therefore, it is understandable why terpene metabolism related proteins, like (E)-4-hydroxy-3-methylbut-2-enyl diphosphate (HMB-PP) reductase and thiolase like protein, both involved in terpenoid synthesis, were differentially expressed by infested P. pinaster (Figure 5A) [30,31]. Subsequently, as the water potential decreases, pine trees suffer severe oxidative stress and here, likewise other PWD-related studies [16,32], several oxidative-related genes were found, namely, a cytochrome c, found in the oxidation of phenolic elements in cell wall polymers under biotic stress, that has been associated with nematode infection in other studies [32] and an aldo/keto reductase, a member of NADPH-dependent oxidoreductases, that intervenes in the elimination of reactive oxygen species produced by plant cells after suffering from a great amount of stress [33]. …”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations